Performance of two selectively bred strains of eastern oyster, Crassostrea virginica, in Delaware Bay, USA with implications for living shoreline features - Hudock, Rileigh E.; Campbell, Brendan; Motz, Noah; Carlisle, Aaron; Hale, Edward (Frontiers in Ecology and Evolution, 2025)
Oyster-based restoration projects, particularly living shorelines, are being installed to protect coastal ecosystems and infrastructure. While these installations often successfully create aquatic habitats, further refinement in optimizing the growth potential of shellfish on shoreline installations will increase the success rate and efficiency of restoration projects. This study evaluated the growth and mortality of two farmed strains of oyster, NEH® (high salinity tolerant) and DBX (medium and low salinity tolerant), in the lower Delaware Bay. From July to October 2023, we monitored the growth and mortality of each strain cultured in rack-and-bag oyster aquaculture gear positioned at intertidal and subtidal environments. The effect of tidal position, temperature, salinity, and dissolved oxygen on oyster performance (average oyster length and weekly oyster mortality) was examined using Generalized Additive Models (GAMs) to determine covariate importance towards the growth and survival of both oyster strains. Our findings indicate that NEH® oysters exhibited better meat condition than DBX oysters, and significantly different average weekly shell length. Oyster weekly average shell length was influenced by average temperature and the previous week’s minimum dissolved oxygen, while weekly mortality was influenced by minimum and average salinity and minimum dissolved oxygen. Subtidal oysters exhibited greater growth and survival than intertidal oysters, suggesting the addition of subtidal design features can enhance the likelihood of success for oyster restoration projects. These results emphasize the need to select an appropriate strain based on local environmental conditions and suggest that pre-seeding selectively bred oysters into living shoreline materials is a viable option to enhance restoration efficiency. Our results aid in our understanding of identifying important physical and environmental factors that determine oyster performance and provide insights via statistical models that can be applied to inform restoration and shellfish-based living shoreline planning.